Memahami Environmental Concern: Analisis Dimensi Egoistic, Altruistic, dan Biospheric pada Peserta Program Sustainable Lifestyle Action 2024 - Nabilah Anggraini Syahputri; Rina Mardiana (IJEEM - Indonesian Journal of Environmental Education and Management, 2026)
The increase of environmental problems has made environmental concern an important aspect in understanding individuals’ concern for environmental issues. This study aims to understand the environmental concern of Sustainable Lifestyle Action (SLA) 2024 participants through an analysis of the egoistic, altruistic, and biospheric dimensions. The study employed a quantitative approach supported by qualitative data. Data were collected through questionnaires and interviews with Sustainable Lifestyle Action 2024 participants and analyzed using descriptive statistics. The findings indicate that the majority of participants were categorized as having high levels across all three dimensions of environmental concern, suggesting a relatively high level of concern toward environmental issues. However, the tendency of these dimensions reflects varying orientations of environmental concern among participants, including personal interests (egoistic), concern for others (altruistic), and concern for ecosystem sustainability (biospheric). This study concludes that the environmental concern of Sustainable Lifestyle Action 2024 participants is multidimensional in understanding environmental issues.